Pengaruh Harga Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Ekami Carwash Lenteng Agung Di Jakarta Selatan - Dimas Saputro Adyatama; Haryantini Haryantini (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to analyze the effect of price and service quality on consumers’ purchasing decisions at Ekami Carwash Lenteng Agung, South Jakarta, motivated by the increasing number of visitors while revenue realization has not yet achieved the company’s target. The population of this study consisted of all Ekami Carwash customers in 2024, totaling 12,854 customers. This research employed a quantitative approach using a survey method by distributing questionnaires to 99 respondents selected through accidental sampling technique. The data were analyzed using multiple linear regression with the assistance of SPSS after passing validity, reliability, and classical assumption tests. The t-test results indicate that price has a positive and significant effect on purchasing decisions with a t-value of 7.497 and an R² of 0.367 (36.7%), meaning that 63.3% is influenced by other factors outside the model. Service quality also has a positive and significant effect with a t-value of 12.084 and an R² of 0.601 (60.1%), while 39.9% is influenced by other variables. Simultaneously, the F-test results show that price and service quality significantly affect purchasing decisions with an F-value of 79.537 and an R² of 0.624, indicating that both variables contribute 62.4% to purchasing decisions. These findings suggest that more competitive pricing and better service quality will increase consumers’ purchasing decisions. Therefore, Ekami Carwash is recommended to maintain competitive pricing and continuously improve service quality to enhance customer satisfaction and overall company performance.